lesSDRF is more: maximizing the value of proteomics data through streamlined metadata annotation - Tine Claeys; Tim Van Den Bossche; Yasset Perez-Riverol; Kris Gevaert; Juan Antonio Vizcaíno; Lennart Martens (Nature Communications, 2023)
Abstract Public proteomics data often lack essential metadata, limiting its potential. To address this, we present lesSDRF, a tool to simplify the process of metadata annotation, thereby ensuring that data leave a lasting, impactful legacy well beyond its initial publication.